The Statesman’s Year-Book World Gazetteer - Paxton, John. author. aut Link
XIII, 693 p.
Keywords: Many improvements have been made to the information. Latitude and longitude references have been added, much more information on capital cities and massive updating of industrial information and population figures. The previous edition was published in 1986.